Critical thinking skills of baccalaureate nursing students at program entry and exit - Thompson, C; Rebeschi, LM (Nursing and Health Care Perspectives, 1999)
Most nurse educators would agree that critical thinking is an essential competency for the professional nurse in today's ever-changing health care environment. In fact, critical thinking has been identified as an integral component of professional nursing practice and has been incorporated in accreditation guidelines (1-3). As a result of this imperative, professional programs of nursing must explicate a clear definition of critical thinking, identify specific learning outcomes reflective of critical thinking abilities, and select appropriate ways to measure the achievement of these outcomes in graduating students. Although much has been written about the need for critical thinking skills, the concept and measurement of critical thinking within the context of nursing education has not yet been clearly defined (4-6). As a result, nursing programs are developing their own conceptual definitions of critical thinking and using a variety of methods to measure outcomes (5). The authors caution that to ensure validity of findings, the instruments used must reflect the individual program's definition of the concept. In most cases, outcomes have been assessed using a cross-sectional design that compares students at different levels or types of programs or are measured as an end-of-program outcome. While such designs can provide educators with knowledge of students' critical thinking abilities at a particular point in the educational process, longitudinal data are needed to assess the effects of the educational program.
tex.unique-id: ISI:000085103900006
Keywords: *Clinical Competence/st [Standards]; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Educational Measurement/mt [Methods]; *Nursing Process; *Program Evaluation/mt [Methods]; *Students; Nursing/px [Psychology]; *Thinking; Accreditation; Clinical Competence; Education; Nursing; Baccalaureate; Educational Measurement; Humans; Nursing Education Research; Nursing Process; Outcome Assessment (Health Care); Outcome Assessment; Health Care; Program Evaluation; Research Design; Students; Nursing; Thinking; accreditation; article; clinical competence; dept.nur; education; health care quality; human; methodology; nursing education; nursing process; nursing student; organization and management; outcome assessment; psychological aspect; standard; thinking; ⛔ No DOI found